Sema3d Restrained Hepatocellular Carcinoma Progression Through Inactivating Pi3k/Akt Signaling via Interaction With FLNA - Li, Yiming; Xu, Cong; Sun, Bo; Zhong, Fangjing; Cao, Momo; Yang, Lianyue (Frontiers in Oncology, 2022)
Hepatocellular Carcinoma (HCC) is one of the most lethal malignant tumors worldwide due to the high incidence rate of metastasis and recurrence. Sema3d has been shown to play critical roles in vascular development during early embryogenesis and several forms of cancer progression via regulating cell migration. However, the function of Sema3d in hepatocellular carcinoma (HCC) remains elusive. This study aimed to explore the function and mechanisms of Sema3d in HCC. In our study, Sema3d expression was significantly downregulated in HCC tissues and cell lines. Downregulated Sema3d expression was closely correlated with aggressive clinicopathological features, poor clinical outcomes of HCC patients. Moreover, overexpression of Sema3d in HCCLM3 cells significantly inhibited and knockdown of Sema3d in PLC/PRF/5 cells promoted proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) of HCC cells in vitro, and tumor growth, EMT, and metastasis in vivo. Further RNA sequencing and GSEA indicated that these phenotypic and function changes were mediated by Pi3k/Akt signaling pathway, and co-IP combined LC-MS indicated Sema3d might interact with FLNA. Finally, we proved that Sema3d exerted its tumor restraining effect by direct combined with FLNA to inactivate Pi3k/Akt signaling pathway and remodel the cytoskeleton. Our data showed that Sema3d restrained hepatocellular carcinoma proliferation, invasion, and metastasis through inactivating Pi3k/Akt via interaction with FLNA, which may serve as a novel prognostic predictor and the potential therapeutic target for HCC patients.